Nosectomia em felinos portadores de carcinoma espinocelular - Relato de sete casos - Huppes, Rafael Ricardo [UNESP]; Nardi, Andrigo Barboza de [UNESP]; Ramirez Uscategui, Ricardo Andres [UNESP]; Pazzini, Josiane Morais [UNESP]; Costa Castro, Jorge Luiz (Univ Estadual Londrina, 2014)
Squamous cell carcinoma is a keratinocytes malignant tumor, the definitive diagnosis of this disease is based on histopathology examination of the lesions. The cats nostrils is one of regions commonly affected by this neoplasm. The response to chemotherapeutic agents, cryosurgery and radiotherapy is poor and for this reason surgical resection is instituted for remove the greatest amount of tissue engaged and provide free margins, in case of nasal involvement are indicated nosectomy often needing reconstructive techniques using as advance flaps for synthesis of surgical wounds. Due to the high incidence of feline patients with this entity, this study aims to report and discuss the effectiveness of nosectomy in seven cats with the disease. It is concluded that nosectomy as a therapeutic technique effective in five of seven cats, resecting tumor margin and providing acceptable time and quality life.
Nosectomy in cats with squamous cell carcinoma - Seven cases report
Keywords: Cat; nostrils; flap; reconstructive surgery